A systematic review and meta‐regression analysis of aggression during the First Episode of Psychosis. (22nd March 2013) - Winsper, C.; Ganapathy, R.; Marwaha, S.; Large, M.; Birchwood, M.; Singh, S. P.
Abstract : Objective: The First Episode of Psychosis (FEP) represents a period of heightened risk for aggression. However, it is not known whether this risk is significantly altered following contact with mental health services. Method: Meta‐analytic methods were used to estimate pooled prevalence of 'any' and 'serious' aggression during FEP, while meta‐regression analyses were conducted to explore reasons for heterogeneity between studies. Results: Fifteen studies comprising 3, 294 FEP subjects were analysed. Pooled prevalence of 'any aggression' before service contact was 28% (95% CI: 22–34) and following contact 31% (95% CI: 20–42). Pooled prevalence of 'serious aggression' was 16% (95% CI: 11–20) before service contact and 13% (95% CI: 6–20) following contact. Four studies reporting repeated assessments within the same cohort revealed that aggression rates did not significantly differ post and pre service contact: Odds Ratios for any aggression: 1.18 (95% CI: 0.46–2.99) and serious aggression: 0.61 (95% CI: 0.31–1.21). Conclusion: Rates of aggression are high during FEP, both before and following initial service contact, and seem not to alter following contact. This conclusion remains tentative due to considerable heterogeneity between studies and a lack of prospective cohort studies.